2014
DOI: 10.1039/c3cp55048f
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative adsorption of 2,3,7,8-TCDD on the surfaces of typical metal oxides: a first-principles density functional theory study

Abstract: The initial dissociative adsorption step of the 2,3,7,8-tetrachlorodibenzo-p-dioxin (2,3,7,8-TCDD) molecule on the surfaces of MgO, CaO, and CuO has been studied by density functional theory (DFT) using periodic slab models. It is found that the 2,3,7,8-TCDD molecule undergoes a similar dissociative adsorption step during the decomposition over the three metal oxide surfaces. The adsorption configuration of 2,3,7,8-TCDD first converts from a parallel mode into a vertical one, then a nucleophilic substitution p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…The optimized parameters of bulk γ-Al 2 O 3 using the non-spinel model were a = 5.595 Å, b = 8.425 Å, and c = 8.072 Å, which were consistent with the experimental values ( a = 5.587 Å, b = 8.413 Å, and c = 8.068 Å) . The cubic crystal structure was selected for CaO and MgO, with optimized parameters of 4.811 and 4.211 Å, respectively, which were also in accordance with the previous results. , …”
Section: Computational Methods and Modelssupporting
confidence: 83%
See 1 more Smart Citation
“…The optimized parameters of bulk γ-Al 2 O 3 using the non-spinel model were a = 5.595 Å, b = 8.425 Å, and c = 8.072 Å, which were consistent with the experimental values ( a = 5.587 Å, b = 8.413 Å, and c = 8.068 Å) . The cubic crystal structure was selected for CaO and MgO, with optimized parameters of 4.811 and 4.211 Å, respectively, which were also in accordance with the previous results. , …”
Section: Computational Methods and Modelssupporting
confidence: 83%
“…Previous studies showed that ZnO (101̅0), γ-Al 2 O 3 (110), CaO (100), and MgO (100) surfaces were the main surfaces of ZnO, γ-Al 2 O 3 , CaO, and MgO. , Therefore, these four surfaces were used in the paper, and the top views of the selected four surfaces were shown in Figure . ZnO (101̅0), γ-Al 2 O 3 (110), CaO (100), and MgO (100) surfaces were modeled using a p (3 × 3) super cell with six layers, p (1 × 2) super cell with four layers, p (3 × 4) super cell with four layers, and p (3 × 4) super cell with four layers.…”
Section: Computational Methods and Modelsmentioning
confidence: 99%
“…In this study, the (100) surface of AEMOs was selected as an ideal model because it is the most stable exposed surface among the various surfaces of AEMOs. , The p (2 × 2) slabs containing four atomic layers were employed. Moreover, the bottom atomic layer was fixed, while the top three atomic layers and the adsorbed species were allowed to relax.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The catalytic oxidation of o-DCB by α-Fe 2 O 3 likely started with the adsorption of o-DCB molecules on α-Fe 2 O 3 surfaces through the binding of Cl atoms to Lewis acid sites (mainly Fe 3+ atoms). 13,16,23,37 The electron-withdrawing effect of Lewis acids can weaken the C-Cl bond, which promotes the dechlorination reaction at low temperatures, 10,20,21 allowing the formation of C x H y O z intermediates and initiating their further oxidation. 22 Understandably, the greater abundance of Lewis acid sites of NR-{110} provided the material higher efficiency in binding and degrading o-DCB.…”
Section: Catalytic Activity Of α-Fe 2 O 3 Under a Dry Condition Is Fa...mentioning
confidence: 99%